CB2 Receptor Deficiency Increases Amyloid Pathology and Alters Tau Processing in a Transgenic Mouse Model of Alzheimer's Disease - Jeremy Koppel; Valerie Vingtdeux; Philippe Marambaud; Cristina d'Abramo; Heidy Jimenez; Mark Stauber; Rachel Friedman; Peter Davies (BMC, 2013)
Abstract The endocannabinoid CB2 receptor system has been implicated in the neuropathology of Alzheimer's disease (AD). In order to investigate the impact of the CB2 receptor system on AD pathology, a colony of mice with a deleted CB2 receptor gene, CNR2, was established on a transgenic human mutant APP background for pathological comparison with CB2 receptor-sufficient transgenic mice. J20 APP (PDGFB-APPSwInd) mice were bred over two generations with CNR2−/− (Cnr2tm1Dgen/J) mice to produce a colony of J20 CNR2+/+ and J20 CNR2−/− mice. Seventeen J20 CNR2+/+ mice (12 females, 5 males) and 16 J20 CNR2−/− mice (11 females, 5 males) were killed at 12 months, and their brains were interrogated for AD-related pathology with both biochemistry and immunocytochemistry (ICC). In addition to amyloid-dependent endpoints such as soluble Aβ production and plaque deposition quantified with 6E10 staining, the effect of CB2 receptor deletion on total soluble mouse tau production was assayed by using a recently developed high-sensitivity assay. Results revealed that soluble Aβ42 and plaque deposition were significantly increased in J20 CNR2−/− mice relative to CNR2+/+ mice. Microgliosis, quantified with ionized calcium-binding adapter molecule 1 (Iba-1) staining, did not differ between groups, whereas plaque associated microglia was more abundant in J20 CNR2−/− mice. Total tau was significantly suppressed in J20 CNR2−/− mice relative to J20 CNR2+/+ mice. The results confirm the constitutive role of the CB2 receptor system both in reducing amyloid plaque pathology in AD and also support tehpotential of cannabinoid therapies targeting CB2 to reduce Aβ; however, the results suggest that interventions may have a divergent effect on tau pathology.